2017
DOI: 10.2135/cropsci2016.10.0907
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Utility of Primed Acclimation for Improving Water Savings in Cotton using a Sensor‐Based Irrigation Scheduling System

Abstract: This study addressed the potential of reduced prebloom irrigation, referred to as primed acclimation (PA), to increase agricultural water-use efficiency (WUE) using a soil-moisture-based irrigation scheduling system in cotton (Gossypium hirsutum L.). To address this, a study was conducted near Camilla, GA, under a variable-rate, center-pivot irrigation system using a Watermark-based automated soil moisture sensing approach to measure soil water potential (SWP) and impose varying irrigation scheduling treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…(Lawlor and Tezara, 2009;Tezara et al, 1999). Although we do not presume that greenhouse experiments will provide identical results to field conditions, these findings highlight the possibility of lasting, negative impacts of drought stress during the prebloom period and illustrate the importance of carefully managing irrigation during the early season based on actual measures of crop water status (Meeks et al, 2017) to minimize drought risk. In the first experiment, when the chlorophyll content was measured, total chlorophyll content per unit leaf area responded positively to increasing drought stress duration, indicating that reductions in chlorophyll content are not associated with drought stress as has been observed in other crop species (Pilon et al, 2018).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…(Lawlor and Tezara, 2009;Tezara et al, 1999). Although we do not presume that greenhouse experiments will provide identical results to field conditions, these findings highlight the possibility of lasting, negative impacts of drought stress during the prebloom period and illustrate the importance of carefully managing irrigation during the early season based on actual measures of crop water status (Meeks et al, 2017) to minimize drought risk. In the first experiment, when the chlorophyll content was measured, total chlorophyll content per unit leaf area responded positively to increasing drought stress duration, indicating that reductions in chlorophyll content are not associated with drought stress as has been observed in other crop species (Pilon et al, 2018).…”
Section: Discussionmentioning
confidence: 83%
“…5 illustrates substantial declines in reproductive DW for all four drought-stressed treatments in 2016, whether water was withheld for 3 wk (followed by a 7-wk recovery) or 6 wk (followed by a 2-wk recovery). Although we do not presume that greenhouse experiments will provide identical results to field conditions, these findings highlight the possibility of lasting, negative impacts of drought stress during the prebloom period and illustrate the importance of carefully managing irrigation during the early season based on actual measures of crop water status (Meeks et al, 2017) to minimize drought risk. Overall, these observations are similar to those of Loka et al (2011) and Loka and Oosterhuis (2012) in which early-season drought stress led to abscission of young squares.…”
Section: Discussionmentioning
confidence: 83%
“…This was attributed to reduced early season evaporation losses and reduced early season plant growth that could not be supported with available irrigation late in the season. Meeks et al (2017) also found that cotton yields were less sensitive to water stress prior to flower bloom in a humid environment. However, this does not mean cotton is completely insensitive to early season water stress.…”
Section: Growth Stage Response To Irrigationmentioning
confidence: 86%
“…Researchers have evaluated the use of electronic monitoring systems for irrigation scheduling under a variety of environmental, cropping, and cultural conditions (Phene et al, 1989;Jones, 2006;Gutiérrez et al, 2013;Haule and Michael, 2014;Soulis et al, 2015;Payero et al, 2017;Fisher et al, 2018Fisher et al, , 2020. Work undertaken explicitly for cotton production has also been reported (Bockhold et al, 2001;Thomson et al, 2002;Bellamy et al, 2009;Leib et al, 2015;O'Shaughnessy et al, 2015;Meeks et al, 2017). Many of these efforts have dealt with development of the electronic systems, field implementation issues, wireless and cellular data transmission, and methods to interpret sensor data and develop scheduling strategies.…”
Section: Soil Sensorsmentioning
confidence: 99%
“…At the same time, the fraction of PAR intercepted by the canopy (IPAR f ) was similar between the various irrigation treatments. In addition to the effect of RUE and IPAR f , total biomass can also be reduced because water deficit hastens maturity (Chastain et al., 2016; Meeks et al., 2017), reducing the number of days over which PAR is intercepted. Regarding excessive irrigation, a study by Bange et al.…”
Section: Introductionmentioning
confidence: 99%